Complete Genome Sequence of a Chikungunya Virus Isolated in Guangdong, China - Li, Xiao-Feng (American Society for Microbiology, 2012)
Chikungunya virus belongs to the genus Alphavirus in the family Togaviridae. Here we report the complete genome sequence of a chikungunya virus strain, GD05/2010, isolated in 2010 from a patient with chikungunya fever in Guangdong, China. The sequence information is important for surveillance of this emerging arboviral infection in China.